Web-Based E-Log Book Application for Enhancing the Quality of Student Projects - Devanda Radya Ananta; Defri Kurniawan (LPPM Universitas Islam 45 Bekasi, 2024)
The student project is the biggest specter for students, and many are hindered by it. The problem that occurs is the difficulty of student activities and assignment supervisors who are still carried out manually, so it cannot be denied that there are many carelessness and errors that have an impact on the final result. The purpose of this research is to design and build a website-based final project guidance e-log book application using the prototyping method in Informatics Engineering S1 Faculty of Computer Science, Dian Nuswantoro University Semarang. The research method applies a qualitative approach with the source of interviews and document studies, while the development method uses the prototype method with three steps namely listening to customers, building and revising mock-ups, and testing. The results showed that the website for recording final project guidance in Informatics Engineering S1, Faculty of Computer Science, Dian Nuswantoro University Semarang that had been developed was in accordance with the needs of the Final Project Coordinator for monitoring students in recording final project guidance. The application of the prototype method that starts from listening to customers, building and revising mock-up, and testing is very helpful in the process of developing a website for recording final project guidance.